2010
DOI: 10.1016/j.otohns.2009.10.049
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of vitamin intake and the risk of hearing loss in men

Abstract: Objective Hearing loss is the most common sensory disorder in the US, afflicting over 36 million people. Higher intakes of vitamins C, E, beta carotene, B12 and folate have been proposed to reduce the risk of hearing loss. Study Design We prospectively evaluated the association between intake from foods and supplements of vitamins C, E, beta carotene, B12, and folate and the incidence of hearing loss. Setting Health Professionals Follow-up Study Subjects and Methods 26,273 men aged 40–75 years at baselin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
56
3
11

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 69 publications
(77 citation statements)
references
References 18 publications
7
56
3
11
Order By: Relevance
“…Moreover, prospective associations between the outcome measure in this study and several risk factors have recently been demonstrated 13,29 . The participants in this cohort are not representative of the adult population in the U.S., but the follow-up rates are high and the information provided is reliable.…”
Section: Discussionmentioning
confidence: 63%
“…Moreover, prospective associations between the outcome measure in this study and several risk factors have recently been demonstrated 13,29 . The participants in this cohort are not representative of the adult population in the U.S., but the follow-up rates are high and the information provided is reliable.…”
Section: Discussionmentioning
confidence: 63%
“…The Panel considers that the available evidence does not establish that modulation of any of these markers is in itself a health outcome, which could be considered as a suitable criterion for deriving a DRV for α-tocopherol. Other studies also investigated the relationship between 'vitamin E'/α-tocopherol and diabetes mellitus (cohort studies (Arnlov et al, 2009;Song et al, 2011)), osteoporosis (one case-control study (Zhang et al, 2006)) and hearing loss (one cohort study (Shargorodsky et al, 2010)). One study (Song et al, 2011) investigated the relationship between the frequency of use (i.e.…”
Section: 'Vitamin E'/α-tocopherol Intake and Health Consequencesmentioning
confidence: 99%
“…The ACEMg treatment was administered to guinea pigs (Le Prell et al 2007 ) and CBA/J mice (Le Prell et al 2011 ) showing reduced permanent threshold shifts after NIHL and also reduced threshold shift after gentamicin ototoxicity (Le Prell et al 2014 ). Studies in humans indicate that regular dietary intake of antioxidants correlates with lower risks of hearing loss (Durga et al 2007 ;Shargorodsky et al 2010 ;Choi et al 2014 ). Chapter 6 by Spankovich discusses epidemiological data on the role of nutrients in hearing loss prevention in humans.…”
Section: Mitochondria Oxidative Stress and Age-related Hearing Lossmentioning
confidence: 99%